Giardia intestinalis: aphidicolin influence on the trophozoite cell cycle - Hofstetrová, Klára; Uzlíková, Magdalena; Tůmová, Pavla; Troell, Karin; Svärd, Staffan G; Nohýnková, Eva (Experimental parasitology, 2010)
This study is a thorough examination of the effects of the DNA polymerase inhibitor aphidicolin on the nuclear cycle and cell cycle progression characteristics, as well as their reversibility, in Giardia intestinalis. Giardia trophozoites are arrested in the G1/S-junction after aphidicolin treatment according to their DNA content. However, cell growth continues and trophozoites arrested with aphidicolin resemble cells in the G2 phase and trophozoites in ageing cultures. Extensive treatment with aphidicolin causes side effects and we detected positive signals for phosphorylated histone H2A, which, in mammalian cells, is involved in a signalling pathway triggered as a reaction to double stranded DNA breaks. These results suggest that aphidicolin causes dissociation of the nuclear and cytoplasmic cycles, a phenomenon that has also been described for other inhibitors in mammalian cell lines. Thus, if aphidicolin is used for synchronization of Giardia trophozoites, this fact must be accounted for, and treatment with aphidicolin must be minimal.
Keywords: Cell Cycle; DNA Damage; Bromodeoxyuridine; cyklin B; průtoková cytometrie; Mitotic Index; Phosphorylation; Time Factors; DNA Replication; replikace DNA; poškození DNA; afidikolin; Nucleic Acid Synthesis Inhibitors; Giardia lamblia; buněčný cyklus; Flow Cytometry; protozoální DNA; histony; inhibitory syntézy nukleových kyselin; Histones; bromodeoxyuridin; Trophozoites; Aphidicolin; časové faktory; mitotický index; Fluorescent Antibody Technique; fosforylace; Cyclin B; DNA, Protozoan; trofozoiti; Enzyme Inhibitors; fluorescenční protilátková technika; inhibitory enzymů